S39. THE IMPACT OF THE GROUP FACTOR ON OUTCOME IN GROUP THERAPY: FINAL RESULTS OF RCT INCLUDING 127 SCHIZOPHRENIA OUTPATIENTS. (18th May 2020) - Mueller, Daniel; Steichen, Conny; Schaller, Kristin; Roder, Volker
Abstract: Background: Today, some evidence-based group therapy approaches focusing different treatment goals are available for the treatment of schizophrenia patients, e.g. psychoeducation, social skills training, CBTp or cognitive remediation. However, only few if any data are available regarding the impact of the group factor as an unspecific mechanism of change regarding outcome in schizophrenia patients. Does the participation in goal-oriented groups per se affect therapy outcome? Methods: To bridge this gap, a cognitive remediation group approach (Integrated Neurocognitive Therapy, INT) developed in our lab has been compared with control patients not participating in therapy groups (Treatment as Usual, TAU). A total of 127 schizophrenia outpatients has been randomly assigned to INT (N=65) or TAU (n=62). INT was conducted twice a week over 15 weeks therapy duration. A comprehensive test battery was assessed before and after therapy as well as at 1-year follow up in both comparison groups. The group factor was assessed by the newly developed questionnaire "Experience and Behavior in Therapy groups EBIT", a brief questionnaire including 13 items. Results: The therapy group showed significantly better effects in EBIT outcome compared to controls regarding the global score (mean of all EBIT items) (GLM: F=4.23, p=.02) as well as regarding empirical 2-factor solution using factor analysis: factor 1 (affect and communication skills) (GLM: F=3.70; p=.03) and factor 2 (eye contact during communication) (F=3.35, p=.04). Additionally, EBIT scores are significantly associated with improvement in cognition and negative symptoms after treatment but not with positive symptoms. Discussion: First of all, the group factor can be identified and measured using a brief questionnaire. Additionally, the group factor has a supplement positive effect on cognition and negative symptoms.